Interface Modification in Three‐Terminal Organic Memory and Synaptic Device. (9th November 2020) - Zheng, Chaoyue; Liao, Yuan; Han, Su‐Ting; Zhou, Ye
Abstract: Interface is a valuable research area for the three‐terminal organic memory device, which is an important member of memory family, as the transport and trapping operation of charge carriers are related to the interfaces between semiconductor/dielectric layers and source‐drain electrodes/semiconductor layer. This progress report highlights the developments of the interface effect for three‐terminal organic memory devices. First, the goals of the interface modification, mainly to adjust the morphology, enhance the adhesion between two layers, change the surface diploes, and regulate the surface energy, are described since the memory characteristic depends on the interfacial property. Second, two common methods are proposed to improve the performance of devices through interface engineering, including fabricating self‐assembled monolayers (SAMs) and thin films with polymers as the interfacial layer. Third, three‐terminal organic memory devices would also be introduced in interfacial engineering since they can be used to simulate various functions of synapses. In the end of this report, the challenges of the interface modification in three‐terminal organic memory devices are discussed. Abstract : The developments of the interface effect for three‐terminal organic memory and synaptic device are highlighted. The goals and two common methods of the interface modification are described and these devices used to simulate various functions of synapses will also be introduced. In the end, the challenges of the interface modification in three‐terminal organic memory devices are discussed.